Speech and Voice Response to a Levodopa Challenge in Late-Stage Parkinson’s Disease - Fabbri, Margherita; Guimarães, Isabel; Cardoso, Rita; Coelho, Miguel; Guedes, Leonor Correia; Rosa, Mario M.; Godinho, Catarina; Abreu, Daisy; Gonçalves, Nilza; Antonini, Angelo; Ferreira, Joaquim J. (Frontiers in Neurology, 2017)
Background: Parkinson’s disease (PD) patients are affected by hypokinetic dysarthria, characterized by hypophonia and dysprosody, which worsens with disease progression. Levodopa’s (L-dopa) effect on quality of speech is inconclusive; no data are currently available for late-stage PD (LSPD). Objective: To assess the modifications of speech and voice in LSPD following an acute L-dopa challenge. Method: LSPD patients (Schwab and England <50/Hoehn Yahr >3 [MED ON]) performed several vocal tasks before and after an acute L-dopa challenge. The following was assessed: respiratory support for speech, voice quality, stability and variability, speech rate and motor performance (MDS-UPDRS-III). All voice samples were recorded and analyzed by a speech and language therapist blinded to patients’ therapeutic condition using Praat 5.1 software. Results: 24/27 (14 men) LSPD patients succeeded in performing voice tasks. Median age and disease duration of patients was 79 [IQR: 71.5-81.7] and 14.5 [IQR: 11-15.7] years, respectively. In MED OFF, respiratory breath support and pitch break time of LSPD patients were worse than the normative values of non-parkinsonian. A correlation was found between disease duration and voice quality (R=0.51; p=0.013) and speech rate (R= -0.55; p=0.008). L-dopa significantly improved MDS-UPDRS-III score (20%), with no effect on speech as assessed by clinical rating scales and automated analysis. Conclusion: Speech is severely affected in LSPD. Although L-dopa had some effect on motor performance, including axial signs, speech and voice did not improve. The applicability and efficacy of non-pharmacological treatment for speech impairment should be considered for speech disorder management in PD.